What will happen to U.S. trade policy when Trump runs the zoo? - Craig VanGrasstek (European Centre for International Political Economy (ECIPE), 2016)
What kind of political animals will be making U.S. trade policy in the Trump administration? The tone of the campaign suggests that the president-elect will act like a bull in the China shop, but his bellicose roars may instead presage a subtler strategy; it is also possible that his own business interests will influence the direction of U.S. policy. His abandonment of free trade and other Republican orthodoxies will force members of that party to decide whether to act like principled elephants or obedient sheep, even while Democrats choose between being opportunistic jackasses or stubborn mules. And in deciding where to direct its trade negotiations, the Trump administration may aim not just for big game like the United Kingdom and Japan, but could also have a few black swans in its sights. These might include such surprising partners as India, Taiwan, the Philippines, MERCOSUR, and perhaps even Russia.
Keywords: 330